Pengaruh Environmental, Social, Governance (ESG) Terhadap Kinerja Keuangan Perusahaan Manufaktur Tahun 2019 - 2022 - Anita Sari; Siti Maryama (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Environmental, Social and Governance (ESG) issues due to company activities have recently become the focus of stakeholder assessments in realizing sustainable companies. The purpose of this study was to determine the effect of Environvental, Social and Governance (ESG) on company financial performance in energy sector companies listed on the IDX in 2019-2022, using ROA as the dependent variable and environmental disclosure, social disclosure and governance disclosure as independent variables. The results of the study are Environmental disclosure (X1) has a positive and significant effect partially on financial performance (Y) with a significance value of 0.017. Social disclosure variables (X2) and governance disclosure have no effect on financial performance (Y) with a significance value showing a negative direction of 0.596 and 0.671. Environmental, social and governance disclosure variables simultaneously affect financial performance with a significance value of 0.003.